If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -5 = 2x + 11 Reorder the terms: -5 + 8x = 2x + 11 Reorder the terms: -5 + 8x = 11 + 2x Solving -5 + 8x = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 8x + -2x = 11 + 2x + -2x Combine like terms: 8x + -2x = 6x -5 + 6x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 6x = 11 + 0 -5 + 6x = 11 Add '5' to each side of the equation. -5 + 5 + 6x = 11 + 5 Combine like terms: -5 + 5 = 0 0 + 6x = 11 + 5 6x = 11 + 5 Combine like terms: 11 + 5 = 16 6x = 16 Divide each side by '6'. x = 2.666666667 Simplifying x = 2.666666667
| 47=c-31 | | X^2+10x-11x=0 | | w/-6=-9 | | a-16=12 | | 45=79-h | | 7c+3=17 | | 45=54-d | | 47=54-d | | (8Z^2)+14z+5=0 | | 62=81-r | | 12i+7r-14i= | | 12i+7r-14y= | | 3t+1=7t | | 6a^2-13a+15=6a | | 95-b=73 | | 0=2x^2-20+50 | | f-25=25 | | 19t+5-17t=23 | | 1/10s= | | v-39=22 | | 28=35-a | | 4x^2=484 | | 3*1/5 | | 7x-y+8x+5y= | | 480ms= | | 6x+10=5x+16 | | 62=92-s | | 9+24=-4 | | 26=u-17 | | 45-3x=9-9x | | 46-j=31 | | 4x^2-20x+26=1 |